Analisis Peran Ganda Perempuan dan Stres Kerja pada Kualitas Kerja Karyawati PT Unggulrejo Wasono (Progress, 2025)
This study aims to analyze the impact of women’s dual roles and work stress on the work quality of female employees in the Production Division of PT Unggulrejo Wasono, Purworejo. The background of this research arises from the phenomenon of married female workers who must balance household responsibilities with factory production demands, a condition that often leads to stress and decreased work performance. Using a qualitative approach, data were collected through observation, in-depth interviews, and documentation, and analyzed using Miles and Huberman’s interactive model. The findings reveal that dual roles significantly influence work quality, with many female employees experiencing physical and mental fatigue that lowers concentration, accuracy, and productivity. Work stress is triggered by excessive workloads, high production targets, uncomfortable working conditions, and limited interpersonal support. There are three findings: (1) negative impacts on female employees without family support; (2) dual roles serve as a motivator when supported by spouses or parents; and (3) fluctuating effects depending on household and work conditions. The research implications affirm that PT Unggulrejo Wasono's efforts to address dual roles and work stress remain limited but somewhat helpful. Counseling programs and stress management training have had a positive impact on some female employees, although the effects are not yet widespread due to the absence of structural policies such as workload adjustments or childcare support. As a result, the work quality of employees who receive support tends to be more stable, while those without support remain vulnerable to decreased productivity and increased absenteeism. Therefore, while the existing efforts are beneficial, their effectiveness needs to be improved to achieve broader positive outcomes.